Intervenção no Moderno: Reconhecimento, caracterização e salvaguarda de edificios de habitação plurifamiliar - Luciana da Silva Rocha (2016)
This research aims to recognise and characterise modern multifamily housingbuildings in order to promote their safeguard. From a number of representativeexamples of the Modern Movement architecture in Oporto (1948-1961), theanalysis focuses on the flats as private domestic spaces particularly subjected toobsolescence and transformation. In this ensemble, we examine the relationshipbetween the changes necessary to fulfil current domestic requirements and thepreservation of their authenticity.The research comparatively examines the original projects and the existent,based on primary sources with archival research, secondary sources, visits tocase studies and interviews with the owners, residents and architects. Thus, thespace-functional transformations are systematized and the tolerance to changetested. Also, the patrimonial valorisation of this architectural legacy isconsidered through the observation of the main instruments that contribute totheir study, dissemination and conservation, as well as the analysis of the legalconditions concerning urban renovation and built heritage protection.In addition, contemporary interventions in Geneva are examined in case studieswith different levels of patrimonial protection, leading to the identification ofdifferent intervention strategies. The latter represent answers to domesticcomfort needs with different consequences in the preservation of originalelements.The main goal of this research is to identify and characterize interventionstrategies that result from a set of actions analysed in the case studies, and todevelop instrumentation to guide future interventions, thus raising awareness tothe potential and limitations of different degrees of transformation.